The 'veil' of control: the perceptions and attitudes of UK design-control planners. Issue 2 (March 2019) - Black, Philip; Sonbli, Taki Eddin
Abstract : In the UK, design is regulated through a system of control for the public interest, which aims to promote quality in the built environment. This system is primarily implemented by local planning professionals with political oversight. These agents are afforded high levels of discretion in the interpretation and implementation of policy and guidance, yet little is known about how they perceive this system or operate within it, creating a 'veil' over the decision-making process. This paper engages with the attitudes and perceptions of these agents through in-depth interviews and Q-Methodology, articulating six unique discourses (the Discretionary Champion, the Civic Advocate, the Rule-Breaking Regulator, the Subjective Theorist, the Self-Assured Evaluator and the Prescriptive Pragmatist) that shed light on a contested arena, identifying how planners understand and approach the control of design, utilise their individual agency, and consider their capacity to pass judgement on design matters.